2022
DOI: 10.3389/fpls.2022.827035
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Responses of Plant Functional Traits to Nitrogen Deposition From Dominant Species to Functional Groups and Whole Communities in Alpine Grasslands on the Qinghai-Tibetan Plateau

Abstract: Nitrogen deposition is recognized as one of the major threats to the ecosystem function of alpine grasslands on the Qinghai-Tibetan Plateau (QTP). However, few studies have documented the gradient responses of plant species, functional groups, and communities in alpine grassland ecosystems to various levels of N deposition on the QTP. We applied eight linear mixed-effect models combing acidification, eutrophication, and phosphorus availability to explore if the responses of functional traits (particularly plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…Apparently, the balance among C, N, and P exerted a profound impact on diverse plant functions, which was able to quickly respond to the dynamics of nutrient supply via its physiological adaptability. Previous studies have explored the coupling patterns of plant N and P (Zhou et al, 2020), leaf N and P (Li et al, 2022), and root N and P in alpine grassland (Ma et al, 2020). And they have illustrated that water and heat play a crucial effect in determining the coupling and decoupling process of C, N, and P biogeochemical cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, the balance among C, N, and P exerted a profound impact on diverse plant functions, which was able to quickly respond to the dynamics of nutrient supply via its physiological adaptability. Previous studies have explored the coupling patterns of plant N and P (Zhou et al, 2020), leaf N and P (Li et al, 2022), and root N and P in alpine grassland (Ma et al, 2020). And they have illustrated that water and heat play a crucial effect in determining the coupling and decoupling process of C, N, and P biogeochemical cycles.…”
Section: Introductionmentioning
confidence: 99%
“…A study from the QTP found that the N deposition could shift plant species composition in favor of graminoids ( Shen H. et al, 2022 ). The responses of the functional traits of alpine plants to the N deposition showed cascading effects from dominant species to functional groups and plant communities ( Li et al, 2022 ). A long-term N addition can greatly reduce species richness ( Li S. et al, 2019 ), and NEE may increase under N addition ( Niu et al, 2009 , 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…In alpine meadow, N and P addition significantly affect t plant communities ( Ma et al., 2021 ), soil microbial community and enzyme activities ( Zi et al., 2022 ), and microbial functional genes ( Xiao et al., 2022 ). In alpine steppe, N and P application led to an increase in aboveground biomass ( Li et al., 2021b ), and increased intensity of bacteria and fungi ( Li et al., 2021c ), also affected the plant functional traits ( Li et al., 2022d ). Meanwhile, grazing increased herbage respiration in summer, presumably through stimulation of gross photosynthesis ( Yuan et al., 2022 ), and changed plant community composition and reduced stochasticity of soil microbial community assembly of alpine grasslands ( Li et al., 2022a ).…”
mentioning
confidence: 99%